2022
DOI: 10.1111/ijfs.15732
|View full text |Cite
|
Sign up to set email alerts
|

The role of bacterial nanocellulose mats encapsulated with cinnamaldehyde on chilled meat preservation

Abstract: Summary Chilled meat preservation from microbial contaminants is particularly important during meat storage. In this study, the new antibacterial nanofiber mats based on bacterial nanocellulose (BNC) and cinnamaldehyde (CMD) were fabricated to evaluate their potential on chilled meat preservation. In particular, the release kinetics, bacteriostatic properties, and the effects on chilled meat preservation were evaluated. Scanning electron microscopy demonstrated that CMD was evenly incorporated within the BNC n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…53 This variation was attributed to the fact that pork undergoes stages of stiffness and spoilage after slaughter. 54 During the stiffness stage, pH value decreases due to the anaerobic glycolysis of muscle glycogen and decomposition of adenosine triphosphate. Conversely, during the spoilage stage, pH value rises due to the bacterial and enzymatic production of ammonia, amines, and other basic nitrogen-containing compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…53 This variation was attributed to the fact that pork undergoes stages of stiffness and spoilage after slaughter. 54 During the stiffness stage, pH value decreases due to the anaerobic glycolysis of muscle glycogen and decomposition of adenosine triphosphate. Conversely, during the spoilage stage, pH value rises due to the bacterial and enzymatic production of ammonia, amines, and other basic nitrogen-containing compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Microencapsulation technology: Recently, microencapsulation technology has been utilized to encapsulate functional ingredients in controlled‐release systems before incorporating them into paper to produce functional paper‐based materials (Rungwasantisuk & Raibhu, 2020). This process aids in enhancing their stability and efficacy, controlling the release of volatile molecules, and eliminating undesirable odors (Qiu et al., 2022; Yuan et al., 2023). Microcapsules typically consist of polymers, shell materials, and core substances.…”
Section: The Preparation and Application Of Hydrophobic Antimicrobial...mentioning
confidence: 99%
“…[9,10] In the previous study, we used oxidized bacterial nanocellulose (OBC) with different carboxyl content to prepare antibacterial fresh-keeping pads and the results confirmed that OBCs fresh-keeping pads have good antibacterial properties and freshkeeping effect of cold meat. [11] Antibacterial absorbent mats mainly extend the shelf life of meat products in two ways: first, by absorbing excess moisture in the packaging and second by inhibiting the formation of biofilms. [9,12] Microbial growth is strongly dependent on high water activity levels and excess liquids permeate from meat products, accumulating on the surface of the meat and acting as a medium that provides a suitable growth environment for the proliferation of pathogens and spoilage microorganisms.…”
Section: Introductionmentioning
confidence: 99%